ASOSIASI SPESIES POLINATOR PADA FICUS spp. DI TAMAN WISATA ALAM BATUPUTIH - Elisabet A. Soares; Hard N. Pollo; Reynold P. Kainde (Universitas Sam Ratulangi, 2021)
AbstractFicus is a genus of plants that require external assistance in order to pollinate.Pollination infruit is Ficus highly dependent on various pollinator insects. Thispollinator insect will help the pollination process in Ficus. The purpose of this studywas to determine the pollinator species associated with four species Ficus in theBatuputih Nature Park. This study used a method by tracing the Batuputih Nature Parkarea to collect data on four species Ficus. The results showed that there were 8pollinator species associated with four species Ficus , consisting of 66 pollinators fromthe family Agaonidae, ordo Hymenoptera. Pollination in four species is Ficus not onlycarried out by one pollinator insect species per Ficus but by two or even three pollinatorinsect species and one pollinator species can pollinate more than one species Ficus.2Frequency distribution analysis shows the number of pollinator frequencies foundin four species Ficus. The results of the diversity index analysis showed that thediversity of pollinators in the four species was Ficus low. The regression analysisshowed a very low addition for each increase in one unit diameter, while the results ofthe correlation analysis showed that the diameter of syconia and the number ofpollinator insects were not correlated.Keywords: Association of pollinator species, Ficus spp., Batuputih Nature Park.